Analisis Pelaksanaan Pembelajaran IPA Kelas V SD N 1 Bebalang - Ni Kadek Sinta Ulandari; Ni Wayan Sri Darmayanti; I Ketut Dedi Agung Susanto Putra (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2024)
This research aims to find out how grade 5 students implement science learning at SD N 1 Bebalang. The subjects in this research were 18 people who were class V students. The instruments used were interviews, observation sheets and documentation. The question to be answered in this research is: How is science learning implemented in class 5 of SD N 1 Bebalang?" To answer this question then This research uses a type of qualitative research using methods qualitative descriptive. Meanwhile, in analyzing the data, researchers used quantitative descriptive analysis techniques. Implementation of Class V Science Learning at SD N 1 Bebalang on pedagogical indicators can be categorized as very good, namely before learning the teacher makes a lesson plan, prepares teaching materials and learning media according to the subject being taught. Apart from that, at the stage of implementing science learning currently teachers use learning methods which varies greatly. At the end of science learning, teachers usually provide evaluations in the form of assignments and test questions to measure students' development and understanding of science learning.